ECOLOGIA DE Callithrix penicillata INTRODUZIDOS NA ILHA DE SANTA CATARINA: UM ESTUDO DE LONGO PRAZO - Gonzalez Carvajal, Juliett Maritza (2019)
Callithrix penicillata (black tufted-ear marmoset) is one of the few Brazilian primates that is not threatened with extinction, due to the ease of living in disturbed habitats and environments, which is why populations can be found in the distribution areas of the species and in places where was introduced. It is an endemic primate of Brazil, with an original distribution in the north-east of Brazil, and introduced in areas of the south-east and south of Brazil. It mainly inhabits semi-deciduous forest vegetation, rainforest vegetation and gallery forests. This species presents the largest geographical distribution area in the genus, occurring in different biomes: Caatinga, Cerrado and Atlantic Forest. The objectives of this work were to evaluate population biology, identify activity patterns, quantify the food items consumed and analyze the life areas of Callithrix penicillata in the Córrego Grande Ecological Park (27°35’51.8”S; 48°30’41.7”W), on the Island of Santa Catarina, southern Brazil. This work had previous information taken in three time intervals (2008-09; 2010-11; 2014-15) and with original data (2017-18). Population data were based on the counts of individuals in each monitored group as well as their age groups. The behavioral patterns were evaluated by means of the instantaneous scan sampling, the area of life was estimated by the Minimum Convex Polygon (MPC), grid method (ME) and 95% Kernel methods. Over the 10 years of monitoring, the groups presented a mean of 10.13 ± 3.19 individuals per group, being 5.52 ± 1.93 adults, 1.31 ± 0.65 subadults, 1.60 ± 0.56 young and 1.72 ± 0.99 infants. The most frequent behavioral pattern was feeding with 37.6 ± 6.5% of the records, followed by displacements (32.5 ± 5.3%), inactivity (17.1 ± 5.2%) and social behaviors (12 , 7 ± 3.6%). The most frequent food items were prey animals with 56.8 ± 16.7% of the records, followed by exudates (19.03 ± 6.07%), fruits (13.7 ± 10.1%) supplementary feeding (9 , 2 ± 6.2%) and nectar (1.1 ± 1.8%). The home range presented an average of 5.3 ± 2.3 ha (ME), 6.7 ± 2.6 ha (MPC) and 6.8 ± 3.5ha (Kernel 95%). Variations in the composition of the groups occurred during the ten years of monitoring, due to births, deaths, emigrations and disappearances. The values of the records found for each pattern of activity in the 10 years of monitoring, did not differ from what has been reported in the literature, for the areas of natural geographic distribution of Callithrix penicillata. There were differences in the living areas of the groups over the ten years of monitoring, which could be influenced by the behavioral pattern they performed more frequently.